Group cohesion and coach leadership based on the competitive level of teams in the context of Paraná's indoor soccer. http://dx.doi.org/10.5007/1980-0037.2013v15n1p89 - José Roberto Andrade do Nascimento Junior; Lenamar Fiorese Vieira (Universidade Federal de Santa Catarina, 2013)
The objective of the present study was to analyze the level of group cohesion and coach leadership style of five-a-side soccer teams from the state of Paraná. Participants consisted of 122 athletes of four teams competing at the National League and four teams competing at the Paraná State Championship in 2011, as well as eight coaches. The following instruments were used: the Group Environment Questionnaire, the Leadership Scale for Sports, and a semi-structured interview. Data analysis was performed using the Kolmogorov-Smirnov test, Cronbach's alpha, Mann-Whitney "U" test (p < 0.05), and categorical analysis. The results demonstrated that the State Championship teams showed higher levels of group cohesion when compared to the National League teams; the coaches of the State Championship teams provided more instructions, reinforcement, and social support to athletes, in addition to showing a more democratic style when compared to the National League coaches - these characteristics were also found in the qualitative analysis. We concluded that the performance level (state/national) of the five-a-side soccer teams had an influence on the cohesion level and coaches' leadership style.